1984
DOI: 10.1152/jappl.1984.56.2.464
|View full text |Cite
|
Sign up to set email alerts
|

Ventilatory muscles during exercise in air and oxygen in normal men

Abstract: To determine whether normal ventilatory muscles fatigue during short-term high-intensity exercise, we measured diaphragmatic electromyogram (EMG, esophageal electrode), and pleural (Ppl), gastric (Pga), and transdiaphragmatic (Pdi) pressures in seven normal young men. On separate days, the subjects performed exercise to exhaustion at a constant work load (80% maximum power output) inspiring air or 40% O2. Before and after exercise, Pdimax and maximum expiratory pressure at the mouth (PEmax) were measured. At 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
0
4

Year Published

1986
1986
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(58 citation statements)
references
References 0 publications
4
50
0
4
Order By: Relevance
“…Firstly, the contribution of hypoxaemia to the exercise limitation is still uncertain, and the mechanisms by which oxygen affects exercise performance are complex [6][7][8][9][10][11]. The present study confirmed previous reports showing that the acute effects of oxygen, as well as the effects of training, correlated poorly with lung function parameters or blood gas values at rest or during exercise [5,6,17].…”
Section: Effects Of Oxygen-supplemented Exercise Trainingsupporting
confidence: 87%
See 1 more Smart Citation
“…Firstly, the contribution of hypoxaemia to the exercise limitation is still uncertain, and the mechanisms by which oxygen affects exercise performance are complex [6][7][8][9][10][11]. The present study confirmed previous reports showing that the acute effects of oxygen, as well as the effects of training, correlated poorly with lung function parameters or blood gas values at rest or during exercise [5,6,17].…”
Section: Effects Of Oxygen-supplemented Exercise Trainingsupporting
confidence: 87%
“…These acute effects of oxygen have been observed both in normoxic patients and in patients who are hypoxaemic at rest or during exercise. Several mechanisms may be involved, including reduction in ventilatory response to exercise (reduced ventilatory equivalent for carbon dioxide (V'E/V'CO 2 )) [6], ventilatory muscle recruitment [7] and delayed ventilatory muscle fatigue [8,9], improved aerobic capacity of the working muscles [10] and a reduction in breathlessness [11].…”
mentioning
confidence: 99%
“…2b) as well as absolute values of PTPdi signi®cantly decreased compared to SL, suggesting further recruitment of accessory respiratory muscles to assist impending failure of the diaphragm. These observations are indirectly con®rmed by studies on hyperoxic exercise that showed a decrease of accessory muscle activation compared to normoxic exercise [24].…”
Section: Effects Of High Altitude On Diaphragm Fatiguementioning
confidence: 80%
“…The respiratory muscles are probably weaker and more fatiguable under isocapnic, hypoxic conditions than under hyperoxic, hypercapnic conditions. Even under normoxic conditions, the administration of supplemental 02 during exercise reduces inspiratory muscle fatiguability (Bye, Esau, Walley, Macklem & Pardy, 1984). Hence, one possible explanation for the unique relation of AP1es I to Sa, 2 could be that peak pressure development is limited at a given Sa0°2 in order to avoid uncomfortable sensations associated with the act of breathing and/or to avoid high pressure that might predispose to muscle fatigue (Bellemare & Grassino 1982;Buchler, Magder & Roussos, 1985).…”
Section: Subjectsmentioning
confidence: 99%